Embracing AI in academia: A mixed methods study of nursing students’ and educators’ perspectives on using ChatGPT - Ebtsam Aly Abou Hashish; Sharifah Abdulmuttalib Alsayed; Noura Mohamed Fadl Abdel Razek (PLoS ONE, 2025)
Background The integration of artificial intelligence (AI) tools such as ChatGPT is reshaping academic practice, particularly in nursing education. Understanding how nursing students and educators perceive and interact with ChatGPT is essential for its responsible and effective use in both academic and clinical contexts. This study aimed to explore knowledge, perceptions, attitudes, and concerns related to ChatGPT among nursing students and educators and to identify potential factors associated with its use in academia. Methods A convergent parallel mixed-methods design was conducted at a Saudi nursing college. Quantitative data were collected from a convenience sample of 240 students and 40 nurse educators using validated self-reported questionnaires. Data were analyzed using descriptive statistics, ANOVA, Pearson’s correlation, and regression analysis. Qualitative data were gathered through semi-structured interviews with 20 students and 15 educators and analyzed thematically. Results Participants demonstrated moderate knowledge and generally positive attitudes and perceptions toward ChatGPT. Educators expressed stronger ethical concerns, particularly regarding plagiarism, over-reliance, and data accuracy. Regression analysis demonstrated that knowledge significantly predicted perceptions and attitudes, with strong predictive power (p < 0.001). Also, ChatGPT experience, academic level, and years of experience as significant predictors of knowledge, perceptions, and attitudes (p ≤ 0.05), with ChatGPT experience showing the strongest predictive power. Thematic analysis yielded four main themes and 22 subthemes: uses of ChatGPT, benefits, concerns, and suggestions for improvement. Conclusion ChatGPT holds promising potential in nursing education, supporting academic productivity and digital competence. However, concerns about ethical use, content accuracy, and discipline alignment remain. Integrating AI literacy training, ethical guidelines, and discipline-specific adaptations is essential to maximize ChatGPT’s benefits and support its safe and effective use in nursing academia.